Exploring the relationship between interpersonal communication and use of modern method family planning in the Philippines - David, Clarissa C.; Atun, Jenna Mae L. (2010)
This study seeks to describe the different social influence sources and processes that affect people?s attitudes and behaviors regarding the use of modern methods of family planning and the realization of fertility desires. Through qualitative in-depth interviews and focused group discussions, we found that age, marital status, urban residence and gender are some of the factors that determine the source and direction of social influence. Women?s social networks are generally supportive of modern method use, but their partners are not. Their sources of influence include mothers, sisters and other female members of the extended family. Men?s social networks on the other hand, which consist of brothers and groups of friends, are a venue for the spread of myths and fallacies about condoms and hormonal contraceptives. Community norms about the inappropriateness of premarital sex and of not marrying a woman that one gets pregnant are learned through parents primarily. Implications on interventions campaign planning are discussed.
Includes bibliographical references (pages 35-37).
Keywords: Family planning; Contraception -- Population; Interpersonal communication; Diffusion